Impact of animal sheds on vegetation configuration in Mediterranean landscapes - Papanastasis V.P.; Ghossoub R.; Scarpelo C. (Nutritional and foraging ecology of sheep and goats, 2009)
Animal sheds function as oikospheres, namely focal points, in Mediterranean landscapes. This is because livestock tend to spend more time grazing near them rather than away from them. Consequently, vegetation is impacted differently around animal sheds resulting in the creation of distinct patches. This impact was investigated in a grazed landscape located in Lagadas county, northern Greece. The dominant vegetation type was kermes oak (Quercus coccifera L.) shrublands. Out of a total of 60 sheds found in an area of 150 km2, three representative sheds housing goats or sheep were selected. Two line transects 800 m long each were placed on each shed in opposite directions and plots of 30 x 30 m were identified at distances 0, 50, 100, 200 and 800 m away from the sheds. Within each plot, plant height and ground cover of the various plant functional types were measured. Plant height and cover of the woody species increased as the distance from the sheds increased (P < 0.0064 and P < 0.0193, respectively) while the cover of herbaceous species, both annual and perennial, decreased (P < 0.0320 and P < 0.0049, respectively). The results indicate that animal sheds are a means of opening up dense shrublands by favoring short vegetation (mainly herbaceous) and thus creating a heterogeneous landscape with a high variety of habitats very resistant to wildfires, a major threat to Mediterranean ecosystems.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)